Necessidades formativas de professores de educação básica especial, diversidade e inclusão: interlocuções e desafios - Salgado, Lenice de Fátima Guedes (2018)
This reser was undertaken the objective investigated the Formative Necessities of Teachers of Special Basic Education (PEBE) that act in the perspective of the inclusive education, in the public net, with the purpose of offering subsidies for the permanent formation in service in which such necessities are an object of analysis and reflection. The study is justified so, there is still little explored the forming paper assumed by the Teacher of Special Basic Education and his base of knowledges for the teaching. Allied to that, there is insufficiency of public policies directed to the formation of this professional, considering the complexity of his attributions and the strategic importance of his acting in the attendance and assistance of the school teams, through the development of propositive, formative and informative actions, in a perspective collaborative. The inquiry of qualitative hallmark, it wrapped the realization of the Group of Discussion near seven teachers who act in the Center of Attention to the Social Inclusion - CAIS, in the city of Diadema – SP and the documentary analysis of regulations of the Special Education and of the titles of formation presented by the teachers to the General office of Education for aims of annual removal and functional evolution. The data were analysed under the perspective of the “Analysis of Prose” proposed by André (1983) and they allowed an approximation with the concerns and professional and formative trajectories of the teachers participants. The confirmed theoretical referential system wrapped the recognition of the constant formation as basic element to the quality of the educative action and the interdisciplinary articulation of studies of the Special Education in the perspective of the inclusive Education; Professional Development Teacher; Work Collaborative, Formation and Formative Necessities. The results stand out like present priority formative necessities in the dialogia: contributions of the ethics; studies on Neuroscience and Education; deepening study on learning disabilities accented, Assistive Technology and Bilingualism. The reflection advanced of the identification of the subjects, for the problematization of the values and underlying finalities to the inclusive education and to the process itself of formation. The participants indicated formative strategies and of innovation, which data of the action reconcile with the process investigative, and the search of signification anchored in theoretical referential on inclusive education and basic authors of the education. Also they proposed exchanges and partnerships with the universities, to advise and to qualify the formative process of the team, like resource that can help in the definition of protocols and in the improvement of the internal communication. There were reflected the contributions of the studies of cases of teaching and groups of studies in the construction of attitudes and practices collaborative in interface with the schools, the families, the community and other sectors and services reaching the involvement and the collaboration necessary to the construction of the school culture inclusive